Scientific validation of cardioprotective attribute by standardized extract of Bombyx mori against doxorubicin-induced cardiotoxicity in murine model - Khan, Masood S.; Mhaveer Singh, Mhaveer; Khan, Mohammad A.; Arya, D. S.; Ahmad, Sayeed (Technische Universität Dortmund, 2014)
Doxorubicin (DOX) is an excellent antineoplastic agent used for the treatment of hematological and solid malignancies. The aqueous extract of Bombyx mori (BMAE) contains amino acids and some flavonoids with obvious cardioprot ective effect. The aim of this study was to investigate the possible protective effect of BMAE against DOX-induced cardiotoxicity and its underlying mechanisms on murine model. The metabolic profiling of BMAE was carried out by Ultra Performance Liquid Chromatography-Mass Spectrometry (UPLC-MS) and the amino acid profiling by HPLC method using fluorescence detector (HPLC-FLD). The biochemical parameter like caspase-3, tumor necrosis factor–alpha (TNF—α), interleukin -6 (IL-6), creatine kinase-MB (CK-MB), lactate dehydrogenase (LDH) and malondialdehyde (MDA) were studied. Tissue damage was further evaluated by histopathological studies. The metabolic profiling of BMAE exhibited presence of quercetin 7-O-β-D-glucoside, kaempferol7-O-β-D-glucopyranoside, coumaric acid glucoside, 2-hydroxy-nonadecanoic acid and 9,12-dihydroxy stearic acid as important constituents. The amino acid profile by HPLC-FLD showed presence of 17 amino acids. The BMAE showed prominent free radical scavenging activity when assessed by the H2O2 and super-oxide method. The results of present investigation showed protection against DOX-induced oxid ative stress (lipid peroxidation), by reverting activities of apoptotic markers (caspase-3 and TNF-α), cardiac markers (CK-MB and LDH activities) as well as pro-inflammatory marker IL-6 followed by oral administration of BMAE. In addition, results of histopathology also supported well the above results. It was observed that BMAE protects DOX-induced cardiotoxicity by virtue of its antioxidants possibly by flavonoids and amino acids.
EXCLI Journal ; Vol. 13, 2014
Keywords: Bombyx mori; doxorubicin; amino acids; cardioprotective; antioxidants; 610